The conflictive discourse of density in London's planning system - Matillana, Fabrizio; Livingstone, Nicola (Frontiers in Sustainable Cities, 2023)
Density in planning presents a series of conflicts in its use based on how it is defined and perceived. When codified into planning policy, however, it is conflictive due to how it manages strategic and local planning needs and the subjective experiences of density. This paper researches the evolution of density policy in London, from the density matrix to the current ‘design-led approach’, examining how this conflictive discourse manifests and is resolved within planning practice. An extensive research of planning applications referred to the Mayor of London, known as called-in applications, examines the strategic and local conflicts in a design-led approach. To further enquire on the findings of the extensive research, semi-structured interviews were conducted to design officers across London local authorities to collect their experiences on the practice of density policies and the ‘design-led approach’ in development management. The article addresses the deficiencies in density policy and proposes design-led tools to address the limitations of the current approach.